Mixed Conducting Ceramic Membranes Fundamentals, Materials and Applications - Zhu, Xuefeng; Yang, Weishen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book is intended to bring together into a single book all aspects of mixed conducting ceramic membranes. It provides a comprehensive description of the fundamentals of mixed ionic-electronic conducting (MIEC) membranes from the basic theories and materials to fabrication and characterization technologies. It also covers the potential applications of MIEC membrane technology in industry. This book offers a valuable resource for all scientists and engineers involved in R&D on mixed conducting ceramic membrane technology, as well as other readers who are interested in catalysis in membrane reactor, solid state electrochemistry, solid oxide fuel cells, and related topics. Xuefeng Zhu, PhD, is a Professor at State Key Laboratory of Catalysis, Dalian Institute of Chemical Physics, Chinese Academy of Sciences, China. Weishen Yang, PhD, is the team leader for Membrane Catalysis and New Catalytic Materials and a DICP Chair Professor at State Key Laboratory of Catalysis, Dalian Institute of Chemical Physics, Chinese Academy of Sciences, China.
Introduction to mixed ionic-electronic conducting membranes -- Defect and diffusion -- Ionic conductors and aspects related to high temperature -- Fabrication and characterization of MIEC membranes -- Permeation principle and models -- Perovskite-type MIEC membranes -- Dual-phase MIEC membranes -- Oxygen permeation at intermediate-low temperatures -- Catalysis reactions in MIEC membrane reactors -- Progress on the commercialization of MIEC membrane technology.
Keywords: Electrochemistry; Energy storage; Ceramic materials; Chemistry, Technical; Electrochemistry; Mechanical and Thermal Energy Storage; Ceramics; Industrial Chemistry